Мовна картина світу в українському романтизмі - Юдкін-Ріпун, І. (Студії мистецтвознавчі, 2007)
The approach of treating language as a parallel to life (the so called biolinguistic parallelism of W. Humboldt) haus arises in Ukraine as the continuation of the philosophy of nature (F. Schelling), that of the “philosophy of life” that has been elaborated by D. Vaillansky and M. Maksymovych. The formation of linguistic concepts in Ukraine took place as a representation of the general patriotic movement of an early romanticism.